Pengaruh Pemberian Pupuk Kandang Ayam Terhadap Pertumbuhan dan Hasil Tanaman Sawi Pakcoy (Brassica Chinensis L.) - Inosensius Y. Wedhu; Henderikus Darwin Beja; Yuyun Wahyuni (Universitas Al Asyariah Mandar, 2021)
Sawi Pakcoy (Brassica chinensis L) is one of the horticultural plants of the Brassicaceae family which is still in the same genus as mustard greens and mustard greens, Sawi pakcoy is a plant that is quite popular and widely consumed by the public because it is very good for health and has high nutritional content. The purpose of this study was to determine the effect of giving chicken manure on the growth and yield of pakcoy (Brassica chinensis L.) plants. The method used in this study was a randomized block design (RBD) with four replications and six treatments, namely, P0: 0 tons / ha or without fertilizer, P1: 20 tons / ha, P2: 30 tons / ha, P3: 40 tons / ha, P4: 50 ton / ha, P5: 60 ton / ha. Based on the results of the analysis of variance using a randomized block design (RBD), it was found that the application of chicken manure had no significant effect on plant height, number of leaves, and had a very significant effect on fresh weight of Tan-1, and fresh weight of ha-1. The optimum dose of chicken manure 60 tons / ha is the best treatment for optimal growth and yield of pakcoy (Brassica chinensis L.) plants with an average production of fresh weight ha-1 reaching 52.47 tons ha-1.